MUSIC THERAPY AND ITS IMPACT ON HUMAN HEALTH (Neo Scientific Peer Reviewed Journal, 2023)
The article is based on the history of musical therapy, its approaches, and its use today, and the study of the human body of music therapy and some of its diseases.